2013
DOI: 10.1093/jxb/ert019
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium-induced shoot ethylene production is associated with the inhibition of lateral root formation in Arabidopsis

Abstract: Foliar NH4(+) exposure is linked to inhibition of lateral root (LR) formation. Here, the role of shoot ethylene in NH4(+)-induced inhibition of LR formation in Arabidopsis was investigated using wild-type and mutant lines that show either blocked ethylene signalling (etr1) or enhanced ethylene synthesis (eto1, xbat32). NH4(+) exposure of wild-type Arabidopsis led to pronounced inhibition of LR production chiefly in the distal root, and triggered ethylene evolution and enhanced activity of the ethylene reporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 66 publications
3
51
0
Order By: Relevance
“…Recently, it was shown that diphenyleneiodonium (DPI) treatment might abolish ammonium‐induced H 2 O 2 accumulation (as measured by DAB staining) (Li et al . ). DPI is a potent inhibitor of NADPH oxidase, cell wall POX and mitochondrial complex I (Bolwell et al .…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it was shown that diphenyleneiodonium (DPI) treatment might abolish ammonium‐induced H 2 O 2 accumulation (as measured by DAB staining) (Li et al . ). DPI is a potent inhibitor of NADPH oxidase, cell wall POX and mitochondrial complex I (Bolwell et al .…”
Section: Discussionmentioning
confidence: 97%
“…Seeds were surface sterilized and cold treated at 4°C for 48 h prior to being sown on standard growth medium. The standard growth medium was as described previously (Li et al, 2013) and was composed of 2 mM KH 2 PO 4 , 5 mM NaNO 3, 2 mM MgSO 4 , 1 mM CaCl 2 , 50 mM Fe-EDTA, 50 mM H 3 BO 3 , 12 mM MnSO 4 , 1 mM ZnC1 2 , 1 mM CuSO 4 , 0.2 mM Na 2 MoO 4 , 1% (w/v) Suc, 0.5 g L -1 MES, and 0.8% (w/v) agar (adjusted to pH 5.7 with 1 M NaOH). The day of sowing was considered day 0.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Recently, Reyt et al (2015) showed that excess Fe had no significant effect on LR initiation in the LR branching zone and that ferritins play an important role in LR emergence under excess Fe in this portion of the root, although the authors had not investigated LR development in the root portions near the growing tip of the primary root. Because LR initiation is restricted to specific pericycle cell files adjacent to a xylem pole in the basal region of the meristem (De Smet et al, 2007;Fukaki and Tasaka, 2009), and LR formation in this new growing root portion may be more susceptible to stress stimuli, such as observed with exposure to high NH 4 + and salt (Duan et al, 2013;Li et al, 2013), it is reasonable to suggest that modulation of LR formation near the growing tip of the primary root is critical to the response to excess Fe stress.…”
mentioning
confidence: 99%
“…NH 4 + applied to shoots causes the auxin-influx carrier AUX1 to inhibit lateral-root emergence . Ethylene production in shoots is associated with NH 4 + -mediated lateral-root inhibition (Li et al 2013). The mechanisms underlying hormonal regulation of NH 4 + stress are largely unknown.…”
Section: Introductionmentioning
confidence: 99%